DNA Demethylation by TDG - Dalton, Shannon R. (2012)
DNA methylation has long been considered a very stable DNA modification in mammals that could only be removed by replication in the absence of re-methylation, i.e. by mere dilution of this epigenetic mark (so-called passive DNA demethylation). However, in recent years, a significant number of studies have revealed the existence of active processes of DNA demethylation in mammals, with important roles in development and transcriptional regulation, allowing the molecular mechanisms of active DNA demethylation to be unraveled. Here we review the recent literature highlighting the prominent role played in active DNA demethylation by base excision repair and especially by Thymine DNA Glycosylase.